Necroptosis Contributes to Persistent Inflammation During Acute Leptospirosis - Kundu, Suman; Shetty, Advait; Gomes-Solecki, Maria (Frontiers in Immunology, 2022)
Leptospirosis is an emerging infectious disease. Recently, canine and human leptospirosis outbreaks were reported in California and New York, respectively. In this study we evaluated the role that cell death processes play in the inflammatory response to Leptospira. Groups of male C3H/HeJ mice were infected with pathogenic L. interrogans and non-pathogenic L. biflexa for 24 and 72 hours; inflammatory processes were characterized for apoptosis and necroptosis by flowcytometry of spleen cells and were further assessed for expression of biomarkers of necroptosis through western blot. We found that pathogenic L. interrogans promotes apoptosis in myeloid neutrophils and monocytes at 24h and 72h post-infection, whereas L. biflexa promotes apoptosis of myeloid monocytes only at 24h post-infection. It is interesting that the immune cells undergoing the common programmed cell death pathway (apoptosis) are the cell types which were not increased in frequency in spleen of mice infected with L. interrogans (neutrophils) and L. biflexa (monocytes) in our previous study. The same trend was observed with pathogenic L. interrogans inducing necroptosis of myeloid neutrophils in addition to monocytes and macrophages at 24h and/or 72h post-infection, whereas L. biflexa promoted this pro-inflammatory cell death process in monocytes and macrophages only at 24h post-infection. Thus, early apoptosis and necroptosis of these cell types may explain its absence in frequency in spleen. Furthermore, at 24h and 72h, expression of the necroptosis molecular biomarkers p-MLKL, p-RIP1 and p-RIP3 was increased post infection with pathogenic L. interrogans. These data suggest that the underlying cell death processes involved in immune responses to pathogenic Leptospira contribute directly to persistent inflammation during the early stages of leptospirosis.